2017
DOI: 10.1136/bmjgh-2016-000129
|View full text |Cite
|
Sign up to set email alerts
|

Taking the health aid debate to the subnational level: the impact and allocation of foreign health aid in Malawi

Abstract: ObjectiveCross-national studies provide inconclusive results as to the effectiveness of foreign health aid. We highlight a novel application of using subnational data to evaluate aid impacts, using Malawi as a case study.DesignWe employ two rounds of nationally representative household surveys (2004/2005 and 2010/2011) and geo-referenced foreign aid data. We examine the determinants of Malawi's traditional authorities receiving aid according to health, environmental risk, socioeconomic and political factors. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(29 citation statements)
references
References 23 publications
1
28
0
Order By: Relevance
“…The result shows that there is more than proportionate increase in public investment in healthcare to the tune of 3.179 percent following 1 percent increase in ODA. This finding is line with the result of Lu, Cook & Desmond (2017) and Marty et al (2017) that foreign aid is effective in boosting public healthcare in the long run. On the contrary, broad-based grant impacted negatively on healthcare investment in the long run.…”
Section: Estimation Of the Ardl Modelssupporting
confidence: 89%
“…The result shows that there is more than proportionate increase in public investment in healthcare to the tune of 3.179 percent following 1 percent increase in ODA. This finding is line with the result of Lu, Cook & Desmond (2017) and Marty et al (2017) that foreign aid is effective in boosting public healthcare in the long run. On the contrary, broad-based grant impacted negatively on healthcare investment in the long run.…”
Section: Estimation Of the Ardl Modelssupporting
confidence: 89%
“…Different studies in African countries has been shown that health expenditure from external source was associated with reduced prevalence and severity of diarrhea [26]. It was reducing the prevalence of malaria as well as improved quality of self-reported health and it was also reduced the overall disease severity [27,28].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, by identifying areas that did and did not receive aid within countries, subnational data allow for quasi‐experimental techniques to gauge aid impacts. Using these data, scholars have found a positive association between aid and development (Dreher & Lohmann, ), including reductions in conflict (van Weezel, ); disease severity; diarrhea prevalence (De & Becker, ); malaria prevalence (Marty, Dolan, Leu, & Runfola, ); and neonatal, infant, and child mortality (Kotsadam et al, ).…”
Section: Introductionmentioning
confidence: 99%